A General Regioselective Synthesis of 2,4-Diarylpyrimidines from 2- Thiouracil through Two Orthogonal Cross-Coupling Reactions - Čerňová, Miroslava; Pohl, Radek; Klepetářová, Blanka; Hocek, Michal (Synlett, 2012)
A novel efficient synthesis of 2,4-diarylpyrimidines was developed based on phosphonium-mediated Suzuki coupling of 2-(methylsulfanyl)pyrimidin-4(3H)-one (at position 4) followed by the Liebeskind–Srogl cross-coupling (at position 2) under microwave irradiation.
Keywords: pyrimidines; uracil; cross-coupling; arylation; microwave; palladium